Предмет: Алгебра,
автор: polinapalenkov
Упростите выражение: (x-y)^2-(x-y)*(x+y)=
Ответы
Автор ответа:
4
X^2 - 2xy+y^2-(x^2+xy-xy-y^2)=x^2 - 2xy+y^2-x^2 +y^2 =2y^2-2xy=2(y^2-xy)
Аноним:
2у(у-х)
Автор ответа:
1
(x-y)²-(x-y)*(x+y)=
(х²-2xy+y²)-(x²-y²)=x²-2xy+y²-x²+y²=-2xy+2y²=2y(-x+y)=2y(y-x)
Похожие вопросы
Предмет: Математика,
автор: olagraceva806
Предмет: Русский язык,
автор: whphub
Предмет: Геометрия,
автор: Timtimjfjc
Предмет: Литература,
автор: gomomomo
Предмет: Информатика,
автор: adelyafax